STRATEGI DAKWAH USTADZ TULUS ANJASMARA DALAM MEMAKMURKAN MUSHALLA HUTAGODANG LABUSEL SUMATERA UTARA - Kartini Siregar (Jurnal Komunikasi, 2024)
The background of this research is that in the world of da'wah, teaching how to invite people to the goodness of the world and the hereafter as well as possible without coercion, threats of death, or with erratic violence. The main goal of Islamic da'wah is to realize happiness and prosperity in life in the world and in the hereafter which is blessed by Allah SWT, and the Prophet Muhammad SAW. There are various ways to preach, can use oral, written, print media, or electronic. Along with the development of the times, da'wah developed quite rapidly and significantly, starting from the number of mad`u, the ways and methods of da'wah or the da'wah actors themselves. Da'wah is also a process of communication, but not all communication processes are da'wah, because da'wah is influencing and contains an invitation to invite people to take actions according to religious orders. Ustadz Tulus Anjasmara is one of the preachers domiciled in Hutagodang Labusel, North Sumatra, who often discusses various issues regarding issues of the Islamic religion. Based on the observations made by the author on October 30, 2022, he discussed a lot about nationalism and various current issues that are currently being hotly discussed among the public. Therefore, this study aims to explain what are the da'wah strategies and what are the supporting and inhibiting factors of Ustadz Tulus Anjas Mara's da'wah in Hutagodang, Labuhan Batu Selatan, North Sumatra. This study uses a qualitative method with a qualitative descriptive approach. By using data collection techniques through, observation, interviews and documentation. Where respondents or informants are used as objects in research and become sources of data or information obtained. The results of this study show that: (1). Ustadz Tulus Anjas Mara preaches with a Sentimental, Rational and Sensory da'wah strategy approach. (2). Factors that support Ustadz Tulus Anjas Mara's preaching are strong spiritual, good intellectual, good physical health and sufficient material. (3). Factors that hinder the preaching of Ustadz Tulus Anjas Mara are internal factors which are still a lack of knowledge of the preacher, inadequate staff of the preacher, inappropriate selection of da'wah materials and inappropriate rhetoric. External factors, in which Mad`u (congregants) are not interested in listening to da'wah and the distance between their homes and places of worship is far away